PENGEMBANGAN LEMBAR KEGIATAN SISWA IPS TEMATIK LINGKUNGAN HIDUP DI SMP - Sophia Fatimah; Raden Gunawan Sudarmanto; M. Thoha B.S Jaya (Jurnal Studi Sosial / Journal of Social Studies, 2014)
The aims of the research are (1) to produce a social science worksheet form thematic material based environment at eighth grade of junior high school; (2) to find out the differences of effectiveness social science learning. This research is development of social science worksheet thematic material. It used purposive sampling techniques. This research was done by two stages: evaluation and pre experiment stage. Result product is learning material that is thematic worksheet which was designed based on curriculum 2013. Worksheet consists of material, assignment and pictures. Results of research are: (1) the use of learning material social science worksheet thematic based for environment material at eighth grade of junior high school is more effective than classical learning method. (2) there is  a difference on the improvement of student result study. (3) there is a difference  average of improvement result study between social science worksheet learning material and classical learning method.Tujuan dari penelitian adalah (1) menghasilkan bentuk LKS IPS berbasis tematik  lingkungan hidup SMP; (2) mengetahui perbedaan efektifitas pembelajaran IPS. Jenis penelitian ini adalah pengembangan. Teknik purposive sampling. Penelitian dilakukan dalam 2 tahapan yaitu: (1) tahap penilaian dan (2) tahap uji coba lapangan. Produk yang dihasilkan dalam penelitian adalah bahan ajar yang berbentuk LKS tematik yang didesain mengikuti kurikulum 2013. LKS ini berisi materi, latihan dan gambar. Hasil penelitian ini: (1) Penggunaan bahan ajar LKS IPS berbasis tematik untuk materi lingkungan hidup SMP lebih efektif dibandingkan dengan metode pembelajaran klasikal. (2) Terdapat perbedaan peningkatan hasil belajar siswa. (3) Terdapat perbedaan rata-rata peningkatan hasil belajar antara bahan ajar LKS IPS dengan metode pembelajaran klasikal.Kata kunci: ips, lembar kegiatan siswa, lingkungan hidup, tematik